ON THE PROBLEM OF MUSICAL AND CREATIVE DEVELOPMENT OF STUDENTS OF PEDAGOGICAL UNIVERSITIES IN THE CLASS OF AN ADDITIONAL MUSICAL INSTRUMENT (PIANO) (Web of Teachers: Inderscience Research, 2023)
The article discusses the installation on the perception of musical works in the professional training of a future music teacher.